Observations on the Protection of Refugees in Indonesia - Fithriatus Shalihah; Muhammad Nur (Universitas Lampung, 2021)
Pekanbaru City and Makassar City are areas that serve as refugee shelters in Indonesia. Generally, refugees in Pekanbaru City and Makassar City were only transiting, while the main destination was Australia. However, the Australian Government's strict policies resulted in refugees being held in Indonesia for many years. This research then examines how the protection of refugees in Pekanbaru City and Makassar City towards the granting of refugee rights granted by the Government and international organizations regarding the status of refugees so far. The author uses empirical/sociological legal research methods, which are conducted by observational research, by conducting surveys, and empirical or socio-legal approaches, namely through field observations, interviews, and literature studies. The results of this study found that Indonesia has respected the provisions of international law in protecting refugees in Indonesia. The handling of refugees in Indonesia For the most part, it has worked well in granting refugee rights under the provisions of international conventions on refugee status.